Asian Yearbook of International Law, Volume 4 (1994) - Swan Sik, Ko; Syatauw, J.J.G; Pinto, M.C.W (Asian Yearbook of International Law, 1996)
The Asian Yearbook of International Law is a major refereed publication dedicated to international law issues as seen primarily from an Asian perspective.